Chromoselective Synthesis of Sulfonyl Chlorides and Sulfonamides with Potassium Poly(heptazine imide) Photocatalyst - Markushyna, Yevheniia; Schüßlbauer, Christoph; Ullrich, Tobias; Guldi, Dirk Michael; Antonietti, Markus; Savateev, Aleksandr (Angewandte Chemie International Edition, 2021)
Among external stimuli used to promote a chemical reaction, photocatalysis possesses a unique one-light. Photons are traceless reagents that provide an exclusive opportunity to alter chemoselectivity of the photocatalytic reaction varying the color of incident light. This strategy may be implemented by using a sensitizer capable to activate a specific reaction pathway depending on the excitation light. Herein, we use potassium poly(heptazine imide) (K-PHI), a type of carbon nitride, to generate selectively three different products from S-arylthioacetates simply varying the excitation light and otherwise identical conditions. Namely, arylchlorides are produced under UV/purple, sulfonyl chlorides with blue/white, and diaryldisulfides at green to red light. A combination of the negatively charged polyanion, highly positive potential of the valence band, presence of intraband states, ability to sensitize singlet oxygen, and multi-electron transfer is shown to enable this chromoselective conversion of thioacetates.
CRIS-Team WoS Importer:2021-08-20